2004
DOI: 10.1143/jjap.43.1144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Biasing on (Ba,Sr)TiO3 Films Prepared by Electron Cyclotron Resonance Plasma Sputtering

Abstract: (Ba,Sr)TiO3 (BST) films were deposited by electron cyclotron resonance (ECR) plasma sputtering with mirror confinement. DC bias voltage was applied to Pt/Ti/SiO2/Si substrates during deposition to vary the intensity of bombardment of energetic ions and to modify film properties. BST films deposited on the substrates at floating potential (approximately +20 V) were found to be amorphous, while films deposited on +40 V-biased substrates were crystalline in spite of a low substrate temperature below 648 K. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Indeed, films deposited at V b ¼ À20 V were found to be amorphous from XRD patterns. 4,5) Thus, it is demonstrated that ions with E i > 60 eV (at V b < À20 V) markedly damage and make the deposited film amorphous. On the other hand, the substrate was not heated externally in the film preparation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, films deposited at V b ¼ À20 V were found to be amorphous from XRD patterns. 4,5) Thus, it is demonstrated that ions with E i > 60 eV (at V b < À20 V) markedly damage and make the deposited film amorphous. On the other hand, the substrate was not heated externally in the film preparation.…”
Section: Resultsmentioning
confidence: 99%
“…We have applied a mirror confinement electron cyclotron resonance (ECR) plasma sputtering method, which could enhance the crystallization of SrTiO 3 (STO) thin films on low-temperature substrates owing to the capability of obtaining high plasma density and highly excited neutral and/or ionized particles at a low pressure of 1-2 Â 10 À2 Pa. 4) In our previous results, 4,5) it was suggested that the crystallization of thin films was achieved by the suppression of the bombardment energy of ions to the substrate. However, the behavior of ions incident onto the substrate has not been clarified in detail in the form of ion energy distribution (IED), which plays an important role in the crystallization and morphology of thin films.…”
Section: Introductionmentioning
confidence: 99%